Shadow Banking : Economics and Policy - Claessens, Stijn; Ratnovski, Lev.; Singh, Manmohan (Washington, D.C. : International Monetary Fund, 2012)
This note outlines the basic economics of the shadow banking system, highlights (systemic) risks related to it, and suggests implications for measurement and regulatory approaches.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet